The testing of money neutrality in economic growth of Indonesia - Husen, Amran; Sunâ€™an, Muammil (MEC-J (Management and Economics Journal), 2017)
This study aim is to test the money neutrality in a narrow sense (M1) and a broad sense (M2) to the growth of output (GDP) in Indonesia, both in short term and long term. This research uses quarterly time series data at 2010 - 2016 periods. The analysis tool used is Error Correction Model (ECM). The results show that short-term money supply (M1 and M2) affect on output growth. However, in the long term, only money circulation in a broad sense (M2) affects on output growth, which also means that money is not neutral because it affects the real sector (GDP).Â Keywords: M1, M2, Population, Capital, and Economic Growth.